2012
DOI: 10.1159/000337251
|View full text |Cite
|
Sign up to set email alerts
|

Two-Year Course of Subfoveal Pigment Epithelial Detachment in Eyes with Age-Related Macular Degeneration and Visual Acuity Better than 20/40

Abstract: Purpose: To investigate the course of subfoveal pigment epithelial detachments (PEDs) in eyes with age-related macular degeneration (AMD) and best-corrected visual acuity (BCVA) ≥20/40. Methods: Thirty-seven eyes of 35 patients with a subfoveal PED were divided into an avascular PED group (n = 11), a vascularized PED group due to polypoidal choroidal vasculopathy (PCV, n = 14) and an occult choroidal neovascularization (CNV) group (n = 12). Intravitreal bevacizumab or ranibizumab was given as needed. The BCVA,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 49 publications
1
27
0
Order By: Relevance
“…This is often associated with poor functional long-term outcomes. [29][30][31] It is unknown whether anti-VEGFinduced PED flattening improves the functional outcome. In analogy with the aim of a dry macula, one may be tempted to assume that PED flattening favors functionality.…”
Section: Discussionmentioning
confidence: 99%
“…This is often associated with poor functional long-term outcomes. [29][30][31] It is unknown whether anti-VEGFinduced PED flattening improves the functional outcome. In analogy with the aim of a dry macula, one may be tempted to assume that PED flattening favors functionality.…”
Section: Discussionmentioning
confidence: 99%
“…At 12 months after treatment, there was marked worsening of vision for eyes treated with PDT or PDT and IVT, and mild decreased vision for eyes treated with anti-VEGF injections despite favorable anatomic outcomes. Baba et al 14 reported that of 37 eyes receiving anti-VEGF therapy, there were no changes in visual outcome in eyes with avascular PED but decreased vision in eyes with vPED or PCV despite similar improvement in PED heights at 2 years. On the other hand, Inoue et al 15 reported visual stabilization despite no anatomical correlation after treatment of 56 eyes with PED due to AMD at 12 months.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown variable outcomes associated with anti-VEGF therapy for this condition. 1,[6][7][8][9][10][11][12][13][14][15][16][17][18][19] In 2012, Introini et al 13 studied 132 eyes with vPED or retinal angiomatous proliferation lesions treated with PDT, PDT and intravitreal corticosteroid (IVT),or anti-VEGF therapy over 10 years. At 12 months after treatment, there was marked worsening of vision for eyes treated with PDT or PDT and IVT, and mild decreased vision for eyes treated with anti-VEGF injections despite favorable anatomic outcomes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Furthermore, Baba et al reported that the PED thicknesses were not significantly different after two years of anti-VEGF therapy among three groups with vascularized PED due to CNV, avascular PED and vascularized PED due to polypoidal choroidal vasculopathy (PCV). 25 Comparisons between the PED group and the control group revealed no significant difference in BCVA between the two groups. On the contrary, it was found that the PED group needed a mean of 2.1 more intravitreal injections than the control group in order to reach the same BCVA.…”
Section: Discussionmentioning
confidence: 83%